The Influence Of Vocal Bingo Game On The Ability To Recognize Vowel Letters In Children Aged 4 - 5 Years - Nabila, Sahyla; Komalasari, Dewi; Dewi, Dwi Jayanti Kurnia; Rahmaningrum, Afifah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Recognizing vowel letters is a fundamental component of early childhood literacy development. This study investigates the impact of the vocal bingo game on the ability of children aged 4–5 years to recognize vowel letters. The research was motivated by the low vowel recognition skills observed at TK Muslimat NU 79 Miftahul Huda. A quantitative approach was applied using a quasi-experimental Nonequivalent Control Group Design. The participants were divided into two groups—experimental and control—each comprising 15 children. An observation sheet, tested for validity and reliability, was used to assess vowel recognition. Data analysis included normality, homogeneity, and hypothesis testing using SPSS version 23. The results revealed a significance value of 0.031 (p<0.05), indicating a significant difference between the experimental and control groups. The posttest mean score of the experimental group (18.07) was higher than that of the control group (15.47). These findings suggest that the vocal bingo game is an effective instructional medium for enhancing early literacy skills in young children.